The Influence of Product, Brand Image, and Corporate Cooperation Service on Company Performance - Teguh Daryadi,; Yustinus Rawi Dandono; Setiasih Setiasih (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
- This study aims to determine the effect of product, brand image, price, and corporate cooperation services on company performance in 2016-2021 either partially or simultaneously.Methodology/approach - The data analysis method used multiple linear regression analysis, with 52 respondents. with the coefficient of determination (R2) obtained an adjusted R Square value of 0.660 or 66%, The Slovin formula calculated the data with an error rate of (e) 5%, multiple linear regression analysis, the coefficient of determination (R2), t test, and F test. Findings - 66% of the company's performance variable is explained by product variables, brand image, price, and service, while the remaining 34% is explained by other variables which are not explained in this studyNovelty/value – product and price do not have a partial effect on company performance, while brand image and service have partial effect on company performance but product, brand image, price, and service have a simultaneous influence on company performance.